Hadith #5039 - Sunan Abi Dawud - Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن; Salm bin Nwh bin Aby سالم بن نوح بن أبي; Umar bin Jabir al-Yemami عمر بن جابر اليمامي (Sunan Abi Dawud)
Two men sneezed in the presence of the prophet (May peace be upon him). He said : Allah have mercy on you! To one and not to the other. He was asked: Messenger of Allah! Two persons sneezed. Ahmad’s version has: You invoked a blessing on one of them and left the other. He replied : This man praised Allah, and this man did not praise Allah.
Grade: Sahih